Conductive carbon black, method for producing conductive carbon black, and conductive material
By controlling the physical and chemical characteristics of conductive carbon black, including the specific surface area of nitrogen adsorption, the DBP absorption amount and the full width of the half peak of the Raman scattering peak, the problem of insufficient conductivity of conductive carbon black is solved and excellent conductivity is achieved.
Patent Information
- Application Number
- CN202380015262.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-10-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-10-19
AI Technical Summary
When used as a constituent component of various conductive materials, the conventional conductive carbon black has high compression resistivity and volume resistivity, and the conductivity is insufficient.
By controlling the nitrogen adsorption specific surface area (N2SA) of the conductive carbon black between 50 and 150 m2/g, the DBP absorption amount is between 205 and 300 mL/100 g, and when the excitation wavelength is set to 532 nm, the full width of the half-maximum ΔD of the Raman scattering peak is between 100 and 260 cm-1, the homogeneous condensation of carbon black and the free movement of π electrons is increased.
The excellent conductivity of conductive carbon black in conductive materials is achieved, the compression resistivity and volume resistivity are reduced, and the conductive properties of the material are improved.
Smart Images

Figure CN118556108B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to conductive carbon black, a method for producing conductive carbon black, and a conductive material. Background Art
[0002] In recent years, with the popularity of mobile phones, notebook personal computers, etc., lithium-ion secondary batteries have become a hot topic, and their demand has increased year by year. In current lithium-ion secondary batteries, for the purpose of increasing the efficiency of battery reaction by increasing the electrode area, a coating mixed with electrode active materials, binders, conductive materials, etc. is usually used, and the positive and negative electrodes obtained by coating a strip of metal foil are wound together with a separator to form a form stored in a battery can (see Patent Document 1, etc.).
[0003] Among them, lithium transition metal composite oxides and the like are used as electrode active materials in the positive electrode. When such electrode active materials are alone, they lack electronic conductivity, i.e., electrical conductivity. Therefore, in order to impart electrical conductivity, carbon materials such as highly developed conductive carbon black are added as conductive materials, and dispersed together with a binder (binding material) in a non-aqueous solvent such as N-methyl-2-pyrrolidone to prepare a slurry (see Patent Document 2), which is applied to a metal foil and dried to form a positive electrode.
[0004] On the other hand, as packaging forms for electronic components represented by integrated circuits (ICs) and electronic components using ICs, injection trays, vacuum formed trays, material boxes, carriers (embossed carriers), etc. are used. In order to prevent damage to the electronic components due to static electricity, the following operation is performed: a conductive sheet in which conductive carbon black is dispersed in a resin is stacked on such packaging containers and arranged to reduce the surface resistivity value.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-308845
[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-157846
[0009] Patent Document 3: Japanese Patent Application Publication No. 2020-172602 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] Conductive carbon black is inexpensive and can exhibit uniform and stable conductivity. However, with the progress of product development in recent years, as a compounding component of conductive materials such as electrode materials and conductive sheets, there is a demand for materials that can exhibit better conductivity.
[0012] In this case, the present invention provides conductive carbon black that can exhibit excellent conductivity when used as a constituent component of various conductive materials, a method for producing the conductive carbon black, and a conductive material using the conductive carbon black.
[0013] Solutions for solving problems
[0014] As a carbon black which can suppress heat generation when compounded into a rubber composition and can exhibit further excellent wear resistance, the applicant has previously proposed the following carbon black: when the excitation wavelength is set to 532 nm, the carbon black is used in the range of 1340 to 1360 cm -1 Carbon black whose total active sites, represented by the product of the half-maximum full width (ΔD) of the Raman scattering peak appearing in the range and the specific surface area (N2SA) when nitrogen is adsorbed, are within a specified range (see Patent Document 3).
[0015] The present inventors conceived of using the above carbon black as conductive carbon black, but found that the above carbon black had high compression resistivity and even volume resistivity and poor conductivity when used as a constituent component of various conductive materials.
[0016] Therefore, in order to solve the above technical problems, the present inventors conducted further research and found that the above technical problems can be solved by using the following carbon black as conductive carbon black, wherein the carbon black has a nitrogen adsorption specific surface area (N2SA) of 50 to 150 m 2 / g, DBP absorption is 205~300mL / 100g, when the excitation wavelength is set to 532nm, at 1340~1360cm -1 The full width at half maximum of the Raman scattering peak in the range of 100 to 260 cm -1 , based on this insight, the present invention has been completed.
[0017] That is, the present invention provides the following solutions:
[0018] (1) A conductive carbon black, characterized in that:
[0019] Nitrogen adsorption specific surface area (N2SA) is 50~150m 2 / g,
[0020] The absorption of DBP is 205-300 mL / 100 g.
[0021] When the excitation wavelength is set to 532nm, the -1 The full width at half maximum of the Raman scattering peak in the range of 100 to 260 cm -1 ;
[0022] (2) A method for producing conductive carbon black, characterized in that it is the method for producing conductive carbon black described in (1) above, wherein:
[0023] A reactor is used in which a fuel combustion zone, a raw material introduction zone and an additive oil introduction zone are sequentially arranged from upstream to downstream of a gas flow path.
[0024] In the aforementioned fuel combustion zone, oxygen-containing gas and fuel are introduced and mixed and burned to generate a high-temperature combustion gas flow. In the aforementioned raw material introduction zone, raw material oil and oxygen-containing gas are introduced while introducing the high-temperature combustion gas flow to generate a primary reaction product. Then, the additional oil is introduced into the additional oil introduction zone to perform a secondary reaction. At this time,
[0025] The oxygen amount of the oxygen-containing gas introduced into the feedstock introduction zone is 0.05 to 0.20 Nm / kg of feedstock oil. 3 introducing the feedstock oil and the oxygen-containing gas in a manner; and,
[0026] (3) A conductive material comprising the conductive carbon black described in (1) above.
[0027] Effects of the Invention
[0028] According to the present invention, there are provided conductive carbon black that can exhibit excellent conductivity when used as a constituent component of various conductive materials, a method for producing the conductive carbon black, and a conductive material using the conductive carbon black. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an explanatory diagram showing a method for calculating the full width at half maximum of ΔD in the conductive carbon black of the present invention.
[0030] Figure 2 This is a diagram showing an example of measuring the Raman spectrum of the conductive carbon black of the present invention.
[0031] Figure 3 A schematic cross-sectional view showing an example of the shape of a reactor used in the method for producing carbon black of the present invention.
[0032] Figure 4 1 is a Raman spectrum diagram obtained in the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0033] First, the conductive carbon black of the present invention will be described.
[0034] The conductive carbon black of the present invention is characterized in that
[0035] Nitrogen adsorption specific surface area (N2SA) is 50~150m 2 / g,
[0036] The absorption of DBP is 205-300 mL / 100 g.
[0037] When the excitation wavelength is set to 532nm, the -1 The full width at half maximum of the Raman scattering peak in the range of 100 to 260 cm -1 .
[0038] The conductive carbon black of the present invention has a nitrogen adsorption specific surface area (N2SA) of 50 to 150 m 2 / g.
[0039] The conductive carbon black of the present invention can suppress homogeneous aggregation (Homoaggregation) of the carbon blacks by having a nitrogen adsorption specific surface area (N2SA) within the above-mentioned range, and can easily exhibit high conductivity when used as a constituent component of various conductive materials.
[0040] The nitrogen adsorption specific surface area (N2SA) of the conductive carbon black of the present invention is preferably 50 to 150 m2 from the viewpoint of imparting high conductivity. 2 / g, and from the viewpoint of suppressing homogeneous aggregation and imparting high conductivity, 50 to 130 m / g is more preferred. 2 / g, and from the viewpoint of forming a conductive path and imparting high conductivity, 60 to 130 m / g is more preferred. 2 / g.
[0041] N2SA is the amount of nitrogen molecules adsorbed per unit mass of carbon black (m 2 N2SA refers to the value determined in accordance with JIS K6217-7:2013 “Test methods for basic properties of carbon black for rubber use” (see ASTM D6556-16).
[0042] The N2SA / IA of the conductive carbon black of the present invention is preferably 0.85×10 3 ~1.10×10 3 m 2 / g.
[0043] Here, N2SA is the nitrogen adsorption specific surface area (m 2 / g), IA is the value of the specific surface area of carbon black expressed by the amount of iodine molecules adsorbed per unit mass of carbon black in the liquid phase (mg / g).
[0044] IA, like N2SA, is an indicator of the specific surface area of carbon black, but is a value that also depends on the amount of surface functional groups of carbon black (the greater the amount of acidic functional groups, the less likely iodine molecules are to be adsorbed, resulting in a value slightly lower than that of N2SA).
[0045] In addition, N2SA / IA, which is obtained by dividing the value of N2SA by the value of IA, is an index representing the surface activity of carbon black. The larger the N2SA / IA value is, the greater the amount of surface functional groups of carbon black is.
[0046] The less the amount of surface functional groups on carbon black, the freer the π electrons can move on the surface of carbon black, thus improving the conductivity. On the other hand, if the surface functional groups are too few, the interaction between carbon black and rubber and resin is not easy to occur, and it becomes easy to cause homogeneous aggregation of carbon blacks, and the conductivity becomes easy to decrease.
[0047] The conductive carbon black of the present invention can suppress homogeneous aggregation of carbon blacks by having N2SA / IA within the above range, and can easily exhibit excellent conductivity when used as a constituent component of various conductive materials.
[0048] The N2SA / IA of the conductive carbon black of the present invention is preferably 0.85×10 3 ~1.10×10 3 m 2 / g, and more preferably 0.85×10 3 ~1.05×10 3 m 2 / g, and more preferably 0.90×10 3 ~1.05×10 3 m 2 / g.
[0049] In addition, in this application document, IA means the value calculated|required based on JIS K6217-1997 "Test method of basic properties of carbon black for rubber use".
[0050] The DBP absorption of the conductive carbon black of the present invention is 205 to 300 mL / 100 g.
[0051] The conductive carbon black of the present invention can be easily produced and provided by having a DBP absorption within the above range, and can easily exhibit high conductivity when used as a constituent component of various conductive materials.
[0052] The DBP absorption of the conductive carbon black of the present invention is 205 mL / 100 g or more from the viewpoint of imparting high conductivity, and preferably 220 mL / 100 g or more from the viewpoint of imparting high conductivity based on the formation of a conductive path. In addition, the DBP absorption of the conductive carbon black of the present invention is preferably 300 mL / 100 g or less, more preferably 250 mL / 100 g or less, and further preferably 236 mL / 100 g or less, in order to suppress the large volume and reduce the clogging in the carbon black capture system.
[0053] The DBP absorption is a value representing the structure of carbon black by the absorption of DBP (dibutyl phthalate) relative to 100 g of carbon black (mL / 100 g).
[0054] In the present application, the DBP absorption refers to a value determined in accordance with JIS K6217-1997 "Test methods for basic properties of carbon black for rubber use".
[0055] The porosity between carbon black aggregates is positively correlated with the structure of carbon black. Therefore, the larger the DBP absorption value, the more developed the structure of carbon black.
[0056] For the conductive carbon black of the present invention, when the excitation wavelength is set to 532 nm, the -1 The full width at half maximum of the Raman scattering peak in the range of 100 to 260 cm -1 .
[0057] The conductive carbon black of the present invention is obtained by setting the excitation wavelength to 532 nm at 1340 to 1360 cm -1 The full width at half maximum ΔD of the Raman scattering peak appearing in the range is within the above range, thereby suppressing the homogeneous aggregation of carbon blacks, and the π electrons on the surface of carbon black become easy to move freely, so that when used as a constituent component of various conductive materials, it can easily exert excellent conductivity.
[0058] In the conductive carbon black of the present invention, when the excitation wavelength is set to 532 nm, the -1 The full width at half maximum ΔD of the Raman scattering peak that appears in the range of 100 to 260 cm is preferably 100 to 260 cm from the viewpoint of imparting high conductivity. -1 , from the viewpoint of suppressing homogeneous aggregation, preferably 120 to 260 cm -1 , from the viewpoint of improving conductivity based on the free movement of π electrons, 120 to 240 cm -1 .
[0059] Figure 1This is a diagram showing a method for calculating the half-width (full-width at half-maximum ΔD) in the conductive carbon black of the present invention (it should be noted that Figure 1 The diagrams are provided as examples to explain the calculation method of the above-mentioned full width at half maximum (full width at half maximum ΔD)).
[0060] like Figure 1 As shown, for the carbon black of the present invention, in the Raman spectrum obtained by measuring at an excitation wavelength of 532 nm using laser Raman spectroscopy, the carbon black of the present invention has a peak at 1340 to 1360 cm -1 (1350±10cm -1 ) is detected with a peak top in the range of .
[0061] Then, the measurement wavelength at the peak position is set to Dmax (cm -1 ), in the obtained spectrum, the detection position on the low wavelength (low Raman shift) side having a detection intensity half of the peak intensity at the above Dmax is set as D50 (cm -1 ) is used as the half maximum width ΔD (cm -1 ).
[0062] ΔD=(Dmax-D50)×2
[0063] In this application document, the full width at half maximum ΔD (cm -1 ) refers to a value calculated from a Raman spectrum obtained by performing data processing (step 2) after measurement under the following measurement conditions (step 1).
[0064] (Step 1) Use HR-800 manufactured by Horiba, Ltd. as a laser Raman spectrometer, place several particles of the carbon black sample to be measured on a glass slide, scrape it several times with a spatula to make the surface flat, and measure the obtained sample under the following measurement conditions.
[0065] YAG laser (excitation wavelength): 532nm
[0066] Number of engraved lines: 600gr / mm
[0067] Filter: D0.6
[0068] Objective lens magnification: 100 times
[0069] Exposure time: 150 seconds
[0070] Cumulative times: 2 times
[0071] The spectrum obtained at this time is shown as an example. Figure 2 .
[0072] (Step 2) The measurement wavelength (Raman Shift) of the obtained spectrum was 2100 cm -1 The signal intensity under the condition of 0 is set, and the average value of every 39 adjacent points in the data points constituting the spectrum is calculated. Then, smoothing is performed to obtain a spectrum curve connecting the above average values. Next, in order to make it easier to compare each sample, the measurement wavelength is 1350±10cm -1 The peak intensity observed in the range of is set to 100. The Raman spectrum obtained at this time is as follows: Figure 1 or Figure 4 Here, the horizontal axis of the graph is the Raman shift (cm -1 ), the vertical axis represents the peak intensity ratio (relative peak intensity ratio) with the peak intensity at Dmax being 100.
[0073] In the above Raman spectrum, at 1340-1360cm -1 (1350±10cm -1 ) corresponds to the peak in the D band of the Raman spectrum.
[0074] According to the research of the inventors, the half-maximum full width ΔD of the peak of the above-mentioned D band represents the degree of disorder of the crystal structure on the surface of carbon black, that is, the crystallinity. The higher the value of the half-maximum full width ΔD of the peak of the above-mentioned D band, the more disordered the crystal structure (the lower the crystallinity).
[0075] It is believed that when the crystallinity is high, there are fewer edges on the carbon black surface, and the π electrons on the carbon black surface move freely, so the conductivity is improved. On the other hand, it is believed that if the crystallinity is too high, the formation sites (active sites) of functional groups on the carbon black surface become fewer, and it is difficult to cause the interaction of carbon black with rubber and resin, and it becomes easy to cause homogeneous aggregation of carbon blacks, and the conductivity is reduced.
[0076] Therefore, in the conductive carbon black of the present invention, by controlling the full width at half maximum ΔD within a predetermined range, it is considered that homogeneous aggregation of carbon blacks is suppressed, and that π electrons become more easily movable, thereby improving conductivity.
[0077] Examples of the method for producing the conductive carbon black of the present invention include the method for producing the conductive carbon black of the present invention described below.
[0078] According to the present invention, it is possible to provide conductive carbon black which can exhibit excellent conductivity when used as a constituent component of various conductive materials.
[0079] Next, the method for producing the conductive carbon black of the present invention will be described.
[0080] The method for producing conductive carbon black of the present invention is characterized in that it is the method for producing conductive carbon black of the present invention described above, wherein:
[0081] A reactor is used in which a fuel combustion zone, a raw material introduction zone and an additive oil introduction zone are sequentially arranged from upstream to downstream of a gas flow path.
[0082] In the aforementioned fuel combustion zone, oxygen-containing gas and fuel are introduced and mixed and burned to generate a high-temperature combustion gas flow. In the aforementioned raw material introduction zone, raw material oil and oxygen-containing gas are introduced while introducing the high-temperature combustion gas flow to generate a primary reaction product. Then, the additional oil is introduced into the additional oil introduction zone to perform a secondary reaction. At this time,
[0083] The oxygen amount of the oxygen-containing gas introduced into the feedstock introduction zone is 0.05 to 0.20 Nm / kg of feedstock oil. 3 The raw oil and oxygen-containing gas are introduced in a manner.
[0084] In this case, as a reactor, a reactor is used in which a fuel combustion zone, a raw material introduction zone, and an additive oil introduction zone are provided in order from the upstream to the downstream direction of the gas flow path. Figure 3 A wide diameter cylindrical reactor is shown schematically.
[0085] Below, we will Figure 3 The reactor shown is used as a suitable example to explain the method for producing the conductive carbon black of the present invention.
[0086] Figure 3 The reactor shown is provided with a fuel combustion zone 3, a raw material introduction zone 5, an additive oil introduction zone 8, and a secondary reaction zone 9 which are connected in order from upstream to downstream of a gas flow path formed in the reactor.
[0087] Right now, Figure 3 In the reactor shown, the fuel combustion zone 3 is provided with: an oxygen-containing gas inlet 1 for introducing oxygen-containing gas such as air from a direction perpendicular to the furnace axis direction; and a combustion burner 2 for supplying fuel in the furnace axis direction. In addition, the raw material introduction and primary reaction zone 5 is provided with: a raw material oil introduction nozzle 4 for supplying raw material oil from a direction perpendicular to the furnace axis direction, which is coaxially connected to the fuel combustion zone 3. Furthermore, the additional oil introduction zone 8 is provided with: an additional oil introduction nozzle 6 for supplying additional oil from a direction perpendicular to the furnace axis direction, which is coaxially connected to the raw material introduction zone 5. The secondary reaction zone 9 is provided coaxially connected to the additional oil introduction zone 8. Figure 3 In the reaction furnace shown, a reaction stop zone is provided coaxially connected to the secondary reaction zone 9, and a coolant introduction nozzle 7 for spraying coolant in a direction perpendicular to the furnace axis direction is provided in the reaction stop zone.
[0088] Figure 3The reactor shown has a drum shape that contracts from the fuel combustion zone 3 toward the raw material introduction zone 5 and expands from the raw material introduction zone 5 toward the additional oil introduction zone 8, but the shape of the reactor is not limited to this shape, and various shapes can be adopted.
[0089] In the method for producing conductive carbon black of the present invention, an oxygen-containing gas and a fuel are introduced into the fuel combustion zone 3 and mixed and burned to generate a high-temperature combustion gas flow.
[0090] Examples of the oxygen-containing gas include oxygen, air, or a mixture thereof, and examples of the fuel include hydrogen, carbon monoxide, natural gas, petroleum gas, FCC residue oil, petroleum-based liquid fuels such as heavy oil, and coal-based liquid fuels such as creosote.
[0091] Examples of the fuel that serves as a generation source of the high-temperature combustion gas include the same fuels as those that can generate the above-mentioned high-temperature combustion gas.
[0092] The supply amount of oxygen-containing gas in the fuel combustion zone 3 is preferably 2000 Nm 3 / h~5500Nm 3 / h, more preferably 2500Nm 3 / h~5000Nm 3 / h, more preferably 3000Nm 3 / h~4500Nm 3 By adjusting the gas supply rate as described above, the flow of the gas in the generator is stabilized, and the conductive carbon black of the present invention can be easily produced.
[0093] The amount of fuel supplied to the fuel combustion zone 3 is preferably 50 kg / h to 400 kg / h, more preferably 100 kg / h to 350 kg / h, and further preferably 150 kg / h to 300 kg / h. By adjusting the amount of fuel supplied as described above, the heat introduced is stabilized, and the conductive carbon black of the present invention can be easily manufactured.
[0094] In the fuel combustion zone 3, for example, an oxygen-containing gas preheated to 400°C to 600°C is supplied, and fuel is supplied so that both are mixed and burned, thereby generating a high-temperature combustion gas flow.
[0095] In the method for producing carbon black of the present invention, the high temperature combustion gas flow is introduced into the raw material introduction zone 5 , and the raw material oil is introduced into the raw material introduction zone 5 from the raw material oil introduction nozzle 4 .
[0096] The raw material oil supplied to the raw material introduction zone 5 may include one or more selected from aromatic hydrocarbons such as cyclohexane, benzene, toluene, xylene, naphthalene, anthracene, etc., coal-based hydrocarbons such as creosote and carboxylic acid oil, petroleum-based heavy oils such as ethylene tar (ethylene heavy-endoil) and FCC residue oil, acetylene-based unsaturated hydrocarbons, vinyl hydrocarbons, pentane, hexane and other aliphatic saturated hydrocarbons, etc.
[0097] In the method for producing carbon black of the present invention, the feedstock oil may be a mixture of two or more of the above-mentioned hydrocarbons.
[0098] In the method for producing carbon black of the present invention, the high-temperature combustion gas flow is introduced into the raw material introduction zone 5 , and the raw material oil and the oxygen-containing gas are simultaneously introduced into the raw material introduction zone 5 .
[0099] Examples of the oxygen-containing gas introduced into the raw material introduction zone 5 together with the raw material oil include oxygen gas, air, or a mixture thereof.
[0100] The oxygen-containing gas introduced into the raw material introduction zone 5 together with the raw material oil can be introduced together with the raw material oil from the raw material oil introduction nozzle 4, or can be introduced separately from the raw material oil from an oxygen-containing gas introduction nozzle provided separately from the raw material oil introduction nozzle 4 (not shown).
[0101] When the oxygen-containing gas is introduced into the raw material introduction zone 5 together with the raw material oil from the raw material oil introduction nozzle 4, for example, a two-fluid nozzle is used as the raw material oil introduction nozzle 4, thereby enabling the introduction of the raw material oil and the oxygen-containing gas.
[0102] For the raw material introduction belt 5, the raw material oil is introduced from the raw material oil introduction nozzle 4, and the oxygen-containing gas is introduced from the oxygen-containing gas introduction nozzle (not shown) separately from the raw material oil. For example, a fluid nozzle is used as the raw material oil introduction nozzle 4 and the oxygen-containing gas introduction nozzle (not shown) respectively, so that the raw material oil and the oxygen-containing gas can be introduced.
[0103] In the method for producing conductive carbon black of the present invention, the high-temperature combustion gas flow is introduced into a raw material introduction zone, and an oxygen-containing gas is introduced into the raw material introduction zone together with the raw material oil, thereby locally forming a high-temperature region in the raw material introduction zone. Then, a primary reaction of the raw material oil is carried out in the raw material introduction zone where the high-temperature region is locally formed, thereby increasing the DBP absorption of the conductive carbon black obtained compared to the case where the oxygen-containing gas is not introduced into the raw material introduction zone, and reducing the DBP absorption at 1340 to 1360 cm when the excitation wavelength is set to 532 nm. -1 By controlling the full width at half maximum ΔD of the Raman scattering peak appearing in the range of , conductive carbon black in which the physical property values are controlled within the desired range can be easily produced.
[0104] The amount of feedstock oil introduced into the feedstock introduction zone 5 is not particularly limited, but is preferably 100 kg / h to 3000 kg / h, more preferably 150 kg / h to 2500 kg / h, and further preferably 200 kg / h to 2000 kg / h. By keeping the amount of feedstock oil introduced within the above range, the nitrogen adsorption specific surface area of the obtained conductive carbon black can be controlled within a desired range.
[0105] The amount of oxygen-containing gas introduced into the raw material introduction zone 5 is not particularly limited, but is preferably 5 Nm 3 / h~600Nm 3 / h, more preferably 8Nm 3 / h~500Nm 3 / h, more preferably 10Nm 3 / h~400Nm 3 / h.
[0106] By keeping the amount of oxygen-containing gas introduced into the raw material introduction zone 5 within the above range, a local high-temperature area can be easily formed in the raw material introduction zone 5, and conductive carbon black can be easily produced whose DBP absorption amount and the half-maximum full width ΔD of the above-mentioned Raman scattering peak are controlled within the desired range.
[0107] In the method for producing conductive carbon black of the present invention, the raw material oil and the oxygen-containing gas are introduced into the raw material introduction belt so that the oxygen content of the oxygen-containing gas is 0.05 Nm / kg of the raw material oil. 3 ~0.20Nm 3 The feedstock oil and oxygen-containing gas are introduced in a manner.
[0108] In the method for producing conductive carbon black of the present invention, the oxygen-containing gas introduction ratio is within the above range, so that a conductive carbon black having an excitation wavelength of 1340 to 1360 cm when the excitation wavelength is 532 nm can be easily produced. -1 Conductive carbon black whose half-maximum full width ΔD of the Raman scattering peak appearing in the range is within a specified range.
[0109] In the method for producing conductive carbon black of the present invention, the amount of oxygen in the oxygen-containing gas is preferably 0.05 Nm3 to 0.20 Nm3 per 1 kg of the feedstock oil from the viewpoint of forming a high temperature region. 3 From the viewpoint of controlling the DBP absorption, 0.07 Nm / kg of feedstock oil is more preferred. 3 From the viewpoint of controlling the full width at half maximum ΔD of the Raman scattering peak, it is more preferably 0.15 Nm / kg of the feedstock oil. 3 the following.
[0110] In the method for producing conductive carbon black of the present invention, when the feedstock oil and the oxygen-containing gas are introduced into the feedstock introduction zone for a primary reaction, the feedstock oil and the oxygen-containing gas are introduced into the feedstock introduction zone preferably in a manner that the reaction temperature is 1300° C. or higher, more preferably in a manner that the reaction temperature is 1500° C. or higher, and in a manner that the reaction temperature is 1800° C. or lower, thereby making it easy to produce. By keeping the reaction temperature in the above range, the DBP absorption amount and the half maximum full width ΔD of the Raman scattering peak can be controlled within the desired range.
[0111] By controlling the reaction temperature in the above-mentioned raw material introduction zone (the reaction temperature during the primary reaction of the raw material oil) to the above-mentioned temperature, it is easy to produce conductive carbon black in which the DBP absorption amount and the half-maximum full width ΔD of the above-mentioned Raman scattering peak are controlled to be within the desired range.
[0112] In the method for producing conductive carbon black of the present invention, after the raw material is introduced and the raw material oil is introduced into the primary reaction zone 5 for primary reaction, the additional oil is introduced into the additional oil introduction zone 8 for secondary reaction.
[0113] The above-mentioned additive oil is preferably a hydrocarbon oil, and examples of the hydrocarbon oil include one or more selected from aromatic hydrocarbons such as cyclohexane, benzene, toluene, xylene, naphthalene, anthracene, etc., acetylenic unsaturated hydrocarbons, vinyl hydrocarbons, aliphatic saturated hydrocarbons such as pentane, hexane, etc.
[0114] In the method for producing conductive carbon black of the present invention, a secondary reaction is carried out by reacting the primary reactant in an amount of added oil that is 0.20 to 0.80 times the mass of the raw oil. In order to ensure stable reactivity, it is preferred to carry out the secondary reaction in an amount that is 0.21 to 0.75 times the mass of the raw oil. In order to ensure stable reactivity and high yield, it is more preferred to carry out the secondary reaction in an amount that is 0.22 to 0.70 times the mass of the raw oil.
[0115] Specifically, the amount of the additional oil introduced into the additional oil introduction zone is preferably 20 to 2400 kg / h, more preferably 30 to 2000 kg / h, and further preferably 40 to 1600 kg / h.
[0116] In the method for producing carbon black of the present invention, by keeping the amount of the added oil within the above-mentioned range, conductive carbon black in which N2SA / IA is controlled within the desired range can be produced with high yield.
[0117] In the method for producing conductive carbon black of the present invention, Figure 3In the case of the reactor shown, after a primary reaction is carried out in the raw material introduction zone 5, the added oil is introduced into the added oil introduction zone 8, and then introduced into the added oil introduction zone 8 and the secondary reaction zone 9 for a secondary reaction, thereby making it easy to prepare the target conductive carbon black.
[0118] In the method for producing conductive carbon black of the present invention, a reactor without the secondary reaction zone 9 may be used, and the secondary reaction may be performed only in the added oil introduction zone 8 .
[0119] Figure 3 In the reactor shown, a carbon black-containing gas is introduced into a reaction stop zone and a coolant is sprayed.
[0120] As the coolant, water or the like can be cited, and by spraying the coolant, the carbon black particles suspended in the high-temperature combustion gas are cooled. The spraying of the coolant can be carried out by, for example, Figure 3 The coolant introduction nozzle 7 shown is carried out by spraying the coolant.
[0121] Next, the cooled carbon black particles are separated and collected by a collection system (separation and collection device) such as a cyclone separator and a bag filter through a flue, etc., thereby recovering the target conductive carbon black.
[0122] In the method for producing conductive carbon black of the present invention, an additional oil is introduced into a primary reactant to carry out the reaction, thereby making it easy to produce conductive carbon black having a predetermined number of edges serving as active sites formed on the surface.
[0123] The details of the conductive carbon black obtained by the production method of the present invention are as described above.
[0124] According to the present invention, there can be provided a method for producing conductive carbon black, which can easily produce conductive carbon black that can exhibit excellent conductivity when used as a constituent component of various conductive materials.
[0125] Next, the conductive material of the present invention will be described.
[0126] The conductive material of the present invention is characterized by containing the conductive carbon black of the present invention.
[0127] The conductive material of the present invention is not particularly limited as long as it contains the conductive carbon black of the present invention.
[0128] Examples of the conductive material of the present invention include electrode materials such as positive electrode materials for lithium ion secondary batteries, and various conductive sheets.
[0129] According to the present invention, there can be provided a conductive material containing the conductive carbon black of the present invention and capable of exhibiting excellent conductivity.
[0130] Next, the present invention will be described in more detail with reference to Examples, but these are merely examples and do not limit the present invention.
[0131] Example
[0132] (Example 1)
[0133] use Figure 3 The reactor shown has a generally cylindrical shape for producing carbon black.
[0134] Figure 3 In the reactor shown, a fuel combustion zone 3, a raw material introduction zone 5, an additive oil introduction zone 8, a secondary reaction zone 9 and a reaction stop zone are provided in sequence from upstream to downstream of a gas flow path formed in the furnace.
[0135] Figure 3 In the reactor shown, the fuel combustion zone 3 is provided with: an oxygen-containing gas inlet 1 for introducing oxygen-containing gas such as air from a direction perpendicular to the furnace axis direction; and a combustion burner 2 for supplying fuel in the furnace axis direction. In addition, the raw material introduction zone 5 is provided with a two-fluid nozzle for supplying raw material oil and oxygen from a direction perpendicular to the furnace axis direction as a raw material oil introduction nozzle 4, which is coaxially connected to the fuel combustion zone 3 and arranged.
[0136] The additional oil introduction zone 8 includes a fluid nozzle that is an additional oil introduction nozzle 6 that supplies additional oil from a direction perpendicular to the furnace axis direction, and is coaxially connected to the raw material introduction and primary reaction zone 5. Furthermore, the secondary reaction zone 9 is coaxially connected to the additional oil introduction zone 8. In addition, the reaction stop zone includes a coolant introduction nozzle 7 (water-cooled quenching) that supplies cooling water from a direction perpendicular to the furnace axis direction and can be changed in position in the vertical direction of the figure, and is coaxially connected to the secondary reaction zone 9.
[0137] like Figure 3 As shown, the reactor is formed into a drum-shaped drawn shape in which the tube gradually contracts from the fuel combustion zone 3 toward the raw material introduction zone 5 and expands into a tapered shape from the raw material introduction zone 5 toward the additional oil introduction zone 8 before and after the raw material introduction zone 5.
[0138] In the fuel combustion zone 3, air (oxygen content 21 volume %) preheated to 500°C was supplied from the oxygen-containing gas inlet 1 at a speed of 4000 Nm 3 / h, and FCC residual oil (petroleum residual oil) as fuel oil is injected and supplied from the combustion burner 2 at 200 kg / h, and mixed and burned to form a high-temperature combustion gas flow flowing along the furnace axis direction.
[0139] The high temperature combustion gas flow is introduced into the raw material introduction zone 5, and FCC residual oil as the raw material oil is supplied at 1500 kg / h from the two-fluid nozzle belonging to the raw material oil introduction nozzle 4, and the flow rate is 100 Nm3 / h of oxygen is supplied, and then, into the additive oil introduction belt 8, cyclohexane is supplied at 370kg / h from the additive oil introduction nozzle 6, and a primary reaction is carried out at a reaction temperature of 1600°C to generate a conductive carbon black-containing gas.
[0140] At this time, the feedstock oil and oxygen introduced into the feedstock introduction zone 5 correspond to a flow rate of 0.07 Nm / kg of feedstock oil. 3 The raw oil and oxygen are introduced in a manner that increases the amount of oxygen.
[0141] Next, the conductive carbon black-containing gas generated through the raw material introduction zone 5 and the added oil introduction zone 8 is introduced into the secondary reaction zone 9, and after further sufficient reaction, it is introduced into the reaction stop zone, and cooling water is sprayed from the coolant introduction nozzle 7. The cooled carbon black particles are collected by a separation and collection device (not shown) through a flue or the like, and the target conductive carbon black is recovered.
[0142] The nitrogen adsorption specific surface area N2SA (m 2 / g), DBP absorption (mL / 100g), IA (mg / g). The obtained results are similar to those of N2SA / IA (×10 3 m 2 / g) are shown in Table 2.
[0143] In addition, the obtained conductive carbon black was measured to have a high conductivity at 1340 to 1360 cm when the excitation wavelength was 532 nm. -1 The full width at half maximum of the Raman scattering peak that appears in the range of ΔD. The Raman spectrum obtained at this time is shown in Figure 4 , and the full width at half maximum ΔD of the Raman scattering peak is shown in Table 2.
[0144] (Example 2 to Example 7, Comparative Example 1 to Comparative Example 9)
[0145] As shown in Table 1, the feedstock oil supply amount (kg / h), oxygen supply amount (kg / h) and oxygen amount (Nm2) per kg of feedstock oil supplied from the feedstock oil introduction nozzle 4 (two-fluid nozzle) to the feedstock introduction zone in Example 1 were changed respectively. 3 ), except for this, a conductive carbon black was prepared in the same manner as in Example 1.
[0146] The nitrogen adsorption specific surface area N2SA (m 2 / g), DBP absorption (mL / 100g), IA (mg / g). The results obtained are similar to those of N2SA / IA (×10 3 m 2 / g) are shown in Table 2.
[0147] In addition, when the excitation wavelength is set to 532 nm, the carbon black obtained has a peak value of 1340 to 1360 cm -1 The full width at half maximum ΔD of the Raman scattering peak appearing in the range is shown in Table 2.
[0148] The conductive carbon blacks obtained in Comparative Examples 5 and 7 had an excitation wavelength of 532 nm at 1340 to 1360 cm -1 The Raman spectrum obtained when the full width at half maximum ΔD of the Raman scattering peak appearing in the range of Figure 4 .
[0149] It should be noted that the conductive carbon black obtained in Comparative Examples 8 and 9 corresponds to the carbon black described in Patent Document 3.
[0150] [Table 1]
[0151]
[0152] Air supply 4000(Nm 3 / h)
[0153] Fuel supply 200 (kg / h)
[0154] Add oil supply 370 (kg / h)
[0155] [Table 2]
[0156]
[0157] <Evaluation 1 (Production of positive electrode material)>
[0158] 1. Preparation of positive electrode materials
[0159] The conductive carbon blacks obtained in Examples 1 to 7 and Comparative Examples 1 to 9 were used to prepare positive electrode materials according to the following method.
[0160] An evaluation sample was prepared by simply mixing 5% by mass of the conductive carbon black and 95% by mass of a commercially available lithium nickel cobalt manganese oxide (NCM811 (made in China)) powder using a shaker.
[0161] 2. Evaluation of electrical conductivity (compression resistivity measurement)
[0162] Using each of the positive electrode materials obtained in 1., positive electrode materials were prepared according to the following method, and the compression resistivity was measured in accordance with JIS K1469 to evaluate the conductivity.
[0163] Using an insulating alumina sleeve (outer diameter 12mm, inner diameter 8mm, length 50mm) and a support fixture for fixing the alumina sleeve, 2g of positive electrode material is filled into the sleeve. The filled sample is compressed with a piston with a force of 1000N, and a current is passed between the samples under a known constant current I (A). The voltage drop E (V) at this time is measured, and the resistance R is calculated based on E÷I. The cross-sectional area S (cm 2 ) is taken as the area of a circle with a diameter of 0.8 cm, the sample height h (cm) during measurement, the position of the displacement gauge on the upper part of the piston after compression when there is no sample as the origin, the position of the displacement gauge on the upper part of the piston after compressing the sample is measured as the sample height, and the compression resistivity ρ (Ω·cm) is calculated according to the following formula.
[0164] ρ=S / h×R
[0165] The results are shown in Table 3.
[0166] <Evaluation 2 (Production of Resin-Blended Conductive Sheet)>
[0167] 1. Preparation of resin compounded conductive sheet
[0168] Using the conductive carbon blacks obtained in Examples 1 to 7 and Comparative Examples 1 to 9, respectively, resin-blended conductive sheets were prepared by the following method.
[0169] To 100 parts by mass of ethylene-vinyl acetate copolymer, 40 parts by mass of conductive carbon black obtained in each example and comparative example was added, and the mixture was kneaded at 120°C for 10 minutes with a blade speed of 50 rpm in a closed mixer (model 10M100), and then vulcanized at 105°C for 15 minutes in a pressurized hot press to obtain a resin compounded sheet.
[0170] 2. Evaluation of electrical conductivity (measurement of volume resistivity)
[0171] The conductivity was evaluated by measuring the volume resistivity VR (Ω·cm) of each of the resin-blended conductive sheets obtained in 1. in accordance with JIS K 6911 (General testing methods for thermosetting plastics). Specifically, the volume resistivity VR (Ω·cm) was determined under the following conditions.
[0172] (Volume resistivity)
[0173] Measuring device: ADCMT digital ultra-high resistance / micro ammeter
[0174] Determination method: double ring electrode method
[0175] Guard electrode: outer diameter 80mm, inner diameter 70mm
[0176] Main electrode diameter: 50mm
[0177] External dimensions of the specimen (vertical × horizontal): 100mm × 100mm
[0178] Sample thickness: 2mm
[0179] Applied voltage: 1V
[0180] Detection current range: 200pA~20mA
[0181] Table 3 shows the logarithm (LogVR) of the measured volume resistivity VR.
[0182] <Evaluation 3 (Production of rubber-blended conductive sheet)>
[0183] 1. Preparation of rubber compound conductive sheet
[0184] Using the conductive carbon blacks obtained in Examples 1 to 7 and Comparative Examples 1 to 9, respectively, rubber-blended conductive sheets were prepared by the following method.
[0185] To 100 parts by mass of EPDM rubber, 30 parts by mass of the conductive carbon black obtained in each of the Examples and Comparative Examples and 1.5 parts by mass of sulfur were added, and the mixture was kneaded at 160° C. for 5 minutes at a blade speed of 85 rpm in a closed mixer (MIXTRON BB-2 manufactured by Kobe Steel Co., Ltd.), and then vulcanized at 150° C. for 40 minutes in a vulcanizing press to obtain a rubber compound sheet.
[0186] 2. Evaluation of electrical conductivity (measurement of volume resistivity)
[0187] Using each of the rubber-combined conductive sheets obtained in 1., the volume resistivity VR (Ω·cm) was measured in accordance with JIS K6271-1:2015 (vulcanized rubber and thermoplastic rubber - method for determining resistivity). Specifically, the volume resistivity VR (Ω·cm) was determined under the following conditions.
[0188] (Volume resistivity)
[0189] Measuring device: ADCMT digital ultra-high resistance / micro ammeter
[0190] Determination method: double ring electrode method
[0191] Guard electrode: outer diameter 80mm, inner diameter 70mm
[0192] Main electrode diameter: 50mm
[0193] External dimensions of the specimen (vertical × horizontal): 100mm × 100mm
[0194] Sample thickness: 2mm
[0195] Applied voltage: 1V
[0196] Detection current range: 200pA~20mA
[0197] Table 3 shows the logarithm (LogVR) of the measured volume resistivity VR.
[0198] [Table 3]
[0199]
[0200] It can be seen from the results in Tables 2 and 3 that the nitrogen adsorption specific surface area (N2SA), DBP absorption and half-maximum full width ΔD of the Raman scattering peak of the conductive carbon black of the present invention obtained in Examples 1 to 7 are respectively within the specified ranges, so that when used as a constituent component of various conductive materials, the compression resistivity and even the volume resistivity are low, and excellent conductivity can be exerted.
[0201] On the other hand, it can be seen from the results in Tables 2 and 3 that any of the nitrogen adsorption specific surface area (N2SA), DBP absorption and half-maximum full width ΔD of the Raman scattering peak of the conductive carbon black obtained in Comparative Examples 1 to 9 are not within the specified range, so when used as a constituent component of various conductive materials, the compression resistivity and even the volume resistivity are high and the conductivity is poor.
[0202] Industrial Applicability
[0203] According to the present invention, there can be provided conductive carbon black that can exhibit excellent conductivity when used as a constituent component of various conductive materials, a method for producing the conductive carbon black, and a conductive material.
[0204] Description of Reference Numerals
[0205] 1 Oxygen-containing gas inlet
[0206] 2 Combustion burners
[0207] 3 Fuel combustion zone
[0208] 4 Raw oil inlet nozzle
[0209] 5. Raw material inlet belt
[0210] 6 Add oil to the nozzle
[0211] 7 Coolant inlet nozzle
[0212] 8 Add oil to the inlet belt
[0213] 9 Secondary reaction zone
Claims
1. A conductive carbon black, characterized in that Nitrogen adsorption specific surface area (N2SA) is 50~150m 2 / g, The absorption of DBP is 205-300 mL / 100 g. When the excitation wavelength is set to 532nm, the -1 The full width at half maximum of the Raman scattering peak in the range of 100 to 260 cm -1 , The N2SA value divided by the IA value gives N2SA / IA, which is 0.85×10 3 ~1.10×10 3 m 2 / g.
2. A method for producing conductive carbon black, characterized in that: The method for producing conductive carbon black according to claim 1, wherein: A reactor is used in which a fuel combustion zone, a raw material introduction zone and an additive oil introduction zone are sequentially arranged from upstream to downstream of a gas flow path. In the fuel combustion zone, oxygen-containing gas and fuel are introduced and mixed and burned to generate a high-temperature combustion gas flow. In the raw material introduction zone, raw material oil and oxygen-containing gas are introduced while the high-temperature combustion gas flow is introduced to generate a primary reaction product. Then, the additional oil is introduced into the additional oil introduction zone to perform a secondary reaction. At this time, The oxygen amount of the oxygen-containing gas introduced into the feedstock introduction zone is 0.05 to 0.20 Nm / kg of feedstock oil. 3 The raw oil and oxygen-containing gas are introduced in a manner.
3. A conductive material, characterized in that: Contains the conductive carbon black according to claim 1.
Citation Information
Patent Citations
Carbon black slurry and lithium secondary battery
JP2003157846A
Electrode for lithium secondary battery and lithium secondary battery using it
JP2003308845A
Carbon black, method for producing carbon black, and rubber composition
JP2020172602A
Preparation method of carbon black capable of improving performance of rubber
CN107304305A
Conductive carbon mixture and method for manufacturing same, electrode using conductive carbon mixture and method for manufacturing same, and electricity storage device provided with electrode
CN110891900A